Diabetes medication regimens and patient clinical characteristics in the national patient‐centered clinical research network, PCORnet. Issue 5 (2nd September 2020) - Bachmann, Katherine N.; Roumie, Christianne L.; Wiese, Andrew D.; Grijalva, Carlos G.; Buse, John B.; Bradford, Robert; Zalimeni, Emily O.; Knoepp, Patricia; Dard, Sofia; Morris, Heather L.; Donahoo, William T.; Fanous, Nada; et al.
Abstract: We used electronic medical record (EMR) data in the National Patient‐Centered Clinical Research Network (PCORnet) to characterize "real‐world" prescription patterns of Type 2 diabetes (T2D) medications. We identified a retrospective cohort of 613, 203 adult patients with T2D from 33 datamarts (median patient number: 12, 711) from 2012 through 2017 using a validated computable phenotype. We characterized outpatient T2D prescriptions for each patient in the 90 days before and after cohort entry, as well as demographics, comorbidities, non‐T2D prescriptions, and clinical and laboratory variables in the 730 days prior to cohort entry. Approximately half of the individuals in the cohort were females and 20% Black. Hypertension (60.3%) and hyperlipidemia (50.5%) were highly prevalent. Most patients were prescribed either a single T2D drug class (42.2%) or had no evidence of a T2D prescription in the EMR (42.4%). A smaller percentage was prescribed multiple T2D drug types (15.4%). Among patients prescribed a single T2D drug type, metformin was the most common (42.6%), followed by insulin (18.2%) and sulfonylureas (13.9%). Newer classes represented approximately 13% of single T2D drug type prescriptions (dipeptidyl peptidase‐4 inhibitors [6.6%], glucagon‐like peptide‐1 receptor agonists [2.5%], thiazolidinediones [2.0%], and sodium‐glucose cotransporter‐2 inhibitors [1.6%]). Among patients prescribed multiple T2D drug types, the most common combination was metformin and sulfonylureas (63.5%). Metformin‐based regimens were highly prevalent in PCORnet's T2D population, whereas newer agents were prescribed less frequently. PCORnet is a novel source for the potential conduct of observational studies among patients with T2D.